Determining the Degree of Burnout among Frontline Nurses in COVID-19 Track and Trace Swabbing Field Teams in Qatar - Romualdo Paul A. Pinca (18507120) (2024)
Background During the COVID-19 pandemic, a series of spikes in COVID-19 cases affected Qatar, increasing efforts to track, isolate, and test close contacts of a confirmed positive case. Consequently, burnout among healthcare workers has been reported. This study examined the degree of burnout among nurses working in the Track and Trace swabbing field teams of the Ministry of Public Health (MoPH) in Qatar, which was responsible for swabbing close contacts of COVID-19 cases in their home and workplace. Methods A descriptive correlational study was conducted to determine the perceived degree of burnout among the nurse participants in terms of Emotional Exhaustion (EE), Depersonalization (DEP), and Personal Accomplishment (PA) using the Maslach Burnout Inventory - Health Services Survey tool. In addition, the demographic profile was also assessed in a standard survey questionnaire. Results Of the 101 nurses, the majority were females (68%) and 74% were from the 31 to 40-year-old age group. The majority were Filipino and Indian nationals, had over 10 years of professional experience, and had been in the swabbing team for more than eleven months (Table1). Only low-to-moderate levels of burnout were reported among the study participants. Most participants experienced low levels of emotional exhaustion (n=81%, x=12.8, SD=9.25) and depersonalization (n=48%, x=5.56, SD=4.64) and moderate levels of personal accomplishment (n=51%, x=38.01, SD=7.26) (Table2). Conclusion Study result suggests that the perceived level of stress experienced by the nurses was manageable. Due to the unpredictability of the COVID-19 situation, it is crucial to conduct regular assessments to prevent burnout from escalating. To manage burnout among nurses in the swabbing team, it is recommended to hold periodic evaluation and debriefing sessions.